Age makes a difference: Symptoms in pediatric supraventricular tachycardia. Issue 5 (13th August 2018) - Quattrocelli, Amanda; Lang, Janet; Davis, Andrew; Pflaumer, Andreas
Abstract: Background: Supraventricular tachycardia is a group of rhythm disturbances that affect 1 in 300‐1200 Australian children annually. The differentiation of supraventricular tachycardia (SVT) symptoms and age of onset according to their subtype is not well understood in the pediatric population. Most studies rely on ECG criteria only to characterize the subtype of the SVT, which is not applicable to all subtypes. The purpose of this study was to identify the symptoms and ages of onset of SVT subtypes, and to analyze whether ethnicity or severity correlated with the SVT subtype confirmed in an invasive Electrophysiology (EP) study. Methods: A retrospective analysis and prospective survey evaluated 364 patients who underwent an EP study at The Royal Children's Hospital, Melbourne between 2009 and 2015. Age of onset, symptoms, and ethnicity were collected by phone survey or medical records in addition to EP study diagnostic data, medication status, and follow‐up information about their symptom status following EP procedure. Patients were grouped according to their SVT subtype. Data analysis was performed using chi‐squared, Fisher's exact, and ANOVA statistical tests to determine associations between SVT substrates. Results: Two hundred and thirty‐three suitable cases of SVT were identified (131 men, 102 women) aged between 0 and 18 years. Atrioventricular Reentrant Tachycardia (AVRT) (n = 153) was the most common SVT subtype, followed by Atrioventricular Nodal Reentrant Tachycardia (AVNRT) (n = 55), Atrial Tachycardia (AT) (n = 17), and other SVT subtypes (n = 8) which included Atrial Fibrillation, Atrial Flutter, and Junctional Tachycardia. There was a male predominance in all subtypes, except for AVNRT. AVNRT patients had palpitations, dyspnoea, dizziness, and anxiety more than any other group, AVRT patients complained of vomiting most and patients with AT had the most fatigue. The mean age of symptom onset varied among groups, being earlier in AVRT, later in AVNRT with a significant difference between AVRT with unidirectional retrograde accessory pathway (URAP) and AVNRT subtypes ( P < 0.01). Conclusion: Some specific symptoms were strong discriminators between different SVT subtypes. Ethnicity did not have strong correlations with SVT subtype incidence. This study was able to show clinical differences among children with SVT due to AVRT (URAP) compared to AVNRT, allowing the prognosis and intended management of pediatric SVT to be anticipated by less invasive means.